Polyurethane Membranes From Red Seaweeds For Ammonia Adsorption - Kamila, Nurul; Marlina, Marlina; Mustafa, Irfan; Nurman, Salfauqi; Saiful, Saiful (Journal of Carbazon, 2023)
Polyurethane (PU) membranes were prepared from red seaweed (Gracilaria sp.), castor oil, Toluene Diisocyanate (TDI), and added benzoyl peroxide (BPO) additive to improve membrane performance. The membrane is applied for the adsorption of ammonia in the solution. FT-IR analysis showed the presence of functional group N = C = O at a wavenumber of 2276 cm-1 and the O-H functional group at a wave number of 3373.50 cm-1, indicating the urethane group's formation has been formed during membrane polymerization. SEM images showed the morphological structure of the PU membrane, where the more open structure of the PU membrane by the addition of BPO. The DSC and TGA results showed the membrane's thermal stability with the addition of BPO. The PU membrane has an optimum contact time for ammonia uptake of 40 minutes. The adsorption isotherm of ammonia by the PU membrane follows the Freundlich isotherm model. The adsorption capacity of the PU membrane with the addition of BPO additives was 13.2 mg/g, which shows that the adsorption capacity of the PU-BPO membrane has a better performance than a membrane without the addition of the BPO. The PU-BPO membrane could be used as an alternative method of ammonia removal.